EFFECT OF SINGLE AND MULTIPLE IMPACT OF HYPOXIC HYPOXIA OF STRONG INTENSITY ON THE STATE OF THE HEMOSTATIC SYSTEM IN RATS - S. V. Moskalenko; I. I. Shakhmatov; Y. A. Bondarchuk; O. M. Ulitina; O. V. Alekseeva (Сибирский научный медицинский журнал, 2019)
The aim of the study was to analyze the state of the reaction of the hemostasis system in rats to a single and multiple exposures to hypoxic hypoxia of strong intensity. Material and methods. Male rats (40 individuals) of the Wistar line were used in the work. Animals have been subjected to a single / daily multiple hypoxic hypoxia by chamber ascent for 1 hour. Hypoxic hypoxia was modeled with the input-outlet chamber. The air discharge created in the pressure chamber in the training mode corresponded to the liftoff to the «height» of 7000 m above sea level (41.105 kPa, 308.3 mm Hg, hypoxia of strong intensity). Results and discussion. A single exposure to the strong intensity of hypoxic hypoxia is characterized by the state of thrombotic readiness (based on the revealed hypercoagulation and high level of markers of intravascular coagulation). The shortening of clot formation start time, increase in the α angle and the maximum bunch density were revealed according to the thromboelastography data. The activation of hemostasis system thrombocytic part, hypercoagulation through the internal clotting path with the thrombinemia signs disappearance have been revealed after completion of the 30-day cycle of severe intensity hypoxia. In addition, the increase in the blood plasma antithrombin reserve was found in the group of experimental animals. The lengthening of clot formation time was recorded by the thromboelastogram results.